Eksplorasi Pengungkapan Corporate Social Responsibility (Csr) Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - Erida Herlina; Linda Sarwanti (BIP's JURNAL BISNIS PERSPEKTIF, 2009)
Corporate Social Responsibility (CSR), is a form of corporete self regulation integrated into a business model. Ideally, CSR policy wouldfunction as a built-in, self-regdating mechanism whereby business would monitor and ensure their adherence to low, ethical standards, and international norms. Business would embrace responsibility for the impact of their activities on the environment, consumers, employees, communities, stakeholders and all other members of the public sphere. Furthermore, business would proactively promote the public interest by encouraging community growth and development, and voluntarily eliminating practices that harm the public sphere, regardless of legality. Essentially, CSR is the deliberate inclusion of public interest into corporate decission making, and the honoring of a triple bottom line: People, Planet, Profit. Some companies use CSR methodologies as a strategic tactic to gain public support for their presence in global markets, helping them sustain a competitive advantage by using their social contributions to provide a subconscious level of advertising. (Fry, Keim, Meiners 1986, 105). This research try to exploing the CSR disclosure in some listed business corporation on Jakarta Stock Exchange by examining the fullfilness CSR items that fit with each companies.